Climate change, biological invasions, and the shifting distribution of Mediterranean fishes: A large‐scale survey based on local ecological knowledge. (20th May 2019) - Azzurro, Ernesto; Sbragaglia, Valerio; Cerri, Jacopo; Bariche, Michel; Bolognini, Luca; Ben Souissi, Jamila; Busoni, Giulio; Coco, Salvatore; Chryssanthi, Antoniadou; Fanelli, Emanuela; Ghanem, Raouia; Garrabou, Joaquim; et al.
Abstract: Climate change and biological invasions are rapidly reshuffling species distribution, restructuring the biological communities of many ecosystems worldwide. Tracking these transformations in the marine environment is crucial, but our understanding of climate change effects and invasive species dynamics is often hampered by the practical challenge of surveying large geographical areas. Here, we focus on the Mediterranean Sea, a hot spot for climate change and biological invasions to investigate recent spatiotemporal changes in fish abundances and distribution. To this end, we accessed the local ecological knowledge (LEK) of small‐scale and recreational fishers, reconstructing the dynamics of fish perceived as "new" or increasing in different fishing areas. Over 500 fishers across 95 locations and nine different countries were interviewed, and semiquantitative information on yearly changes in species abundance was collected. Overall, 75 species were mentioned by the respondents, mostly warm‐adapted species of both native and exotic origin. Respondents belonging to the same biogeographic sectors described coherent spatial and temporal patterns, and gradients along latitudinal and longitudinal axes were revealed. This information provides a more complete understanding of the shifting distribution of Mediterranean fishes and it also demonstrates that adequately structured LEK methodology might be applied successfully beyond the local scale, across national borders and jurisdictions. Acknowledging this potential through macroregional coordination could pave the way for future large‐scale aggregations of individual observations, increasing our potential for integrated monitoring and conservation planning at the regional or even global level. This might help local communities to better understand, manage, and adapt to the ongoing biotic transformations driven by climate change and biological invaders. Abstract : Through a large coordinated effort, we asked fishers from nine Mediterranean Countries to tell us about species perceived to be increasing in abundance or 'new' in their fishing areas. Respondents reported increasing abundances of warm water fishes of both native and exotic origin, contributing to trace back their expansion over the spatiotemporal scale. Assembling this information across national borders and jurisdictions provided us with a regional picture of ongoing biotic transformations, mostly driven by invasive species and by the putative effects of climate change.